Direct and Indirect Costs of Chronic Obstructive Pulmonary Disease in Korea - Changhwan Kim, M.D.; Younhee Kim, Ph.D.; Dong-Wook Yang, Ph.D.; Chin Kook Rhee, M.D.; Sung Kyoung Kim, M.D.; Yong-Il Hwang, M.D.; Yong Bum Park, M.D.; Young Mok Lee, M.D.; Seonglim Jin, M.D.; Jinkyeong Park, M.D.; Cho-Rom Hahm, M.D.; Chang-Han Park, M.D.; et al. (Tuberculosis and Respiratory Diseases, 2019)
Background Understanding the burden of disease is important to establish cost-effective treatment strategies and to allocate healthcare resources appropriately. However, little reliable information is available regarding the overall economic burden imposed by chronic obstructive pulmonary disease (COPD) in Korea.